Responses to the financial crisis, treasury debt, and the impact on short-term money markets - Warren B. Hrung; Jason S. Seligman (Federal Reserve Bank of New York, 2011)
Several programs have been introduced by US fiscal and monetary authorities in response to the financial crisis. We examine the responses involving Treasury debt - the Term Securities Lending Facility (TSLF), the Supplemental Financing Program, increases in Treasury issuance, and open market operations - and their impacts on the overnight Treasury general collateral repo rate, a key money market rate. Our contribution is to consider each policy in light of the others, both to help guide policy responses to future crises and to emphasize policy interactions. Only the TSLF was designed to directly address stresses in short-term money markets by temporarily changing the supply of Treasury collateral in the marketplace. We find that the TSLF is uniquely effective relative to other policies and that, while changes in Treasury collateral do affect reporates, the impacts are not equivalent across sources of Treasury collateral.
Keywords: E50; G01; H60; 330; Treasury debt; repo rates; money markets; financial crisis; monetary policy